Wybrane metody aktywizujące w nauczaniu rachunkowości - Foremna-Pilarska, Monika; Polak, Katarzyna (Selected Activating Methods in Accountancy Teaching, 2005)
The aim of the article is to show the necessity of adopting the activating methods in the accountancy teaching program. The work reveals only two of many activating methods as the most appropriate in the teaching program of this subject. These are: the didactic discussion and situational method. There is also shown in the paper the example of adopting such methods in the accountancy lectures and classes training.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 43-51